Preference of Non-litigation Procedures through Alternative Dispute Resolution in the Settlement of Sharia Economic Disputes - Amran Suadi (APPTHI, 2018)
Besides the settlement of cases through litigation in courts, there is another institution of non-litigation settlements through Alternative Dispute Resolution (ADR). From the normative side, it is clear that alternative dispute resolution is given a wide space to solve disputes between citizens and citizens and the state, especially regarding sharia economic disputes. Law No. 30 of 1999 concerning Arbitration and Alternative Case Resolution regulates dispute resolution outside the Court through Consultation, Negotiation, Mediation, Conciliation, and Expert Assessment. Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution can be said to be the most real and more specific manifestation of the state’s efforts to apply and socialize the institution of peace in sharia business disputes. This law also states that the state gives freedom to the public to resolve their sharia business disputes outside the court, either through consultation, mediation, negotiation, conciliation, or expert judgment. The law is intended to regulate dispute resolution in sharia business disputes outside the court forum by providing the possibility and right for the disputing parties to resolve disputes or differences of opinion between the parties in a forum that is more in line with the parties’ intentions. This forum is expected to accommodate the interests of the disputing parties, especially in terms of sharia economic disputes. Abstrak Cara penyelesaian konflik (perselisihan) antar individu dalam masyarakat selama ini, cenderung lebih banyak dilakukan melalui jalur konvensional yaitu penyelesaian perkara melalui litigasi (pengadilan). Sehingga banyak orang ingin mencari cara lain atau lembaga lain dalam penyelesaian sengketa di luar pengadilan melalui alternatif penyelesaian sengketa. Saat ini penyelesaian sengketa atau konflik sudah mulai bergeser ke penyelesaian non litigasi yang dikenal dengan Alternative Dispute Resolution (ADR). Undang-Undang No. 30 Tahun 1999 tentang Arbitrase dan Alternatif Penyelesaian Perkara mengatur penyelesaian sengketa di luar Pengadilan. yaitu melalui Konsultasi, Negosiasi, Mediasi, Konsiliasi, dan Expert Assessment. Undang-Undang No. 30 Tahun 1999 tentang Arbitrase dan Alternatif Penyelesaian Sengketa dapat dikatakan sebagai wujud paling nyata dan lebih spesifik dari upaya Negara menerapkan dan mensosialisasikan pranata perdamaian dalam sengketa bisnis. Undang-undang ini juga menyatakan bahwa Negara memberikan kebebasan kepada masyarakat untuk menyelesaikan sengketa bisnisnya di luar pengadilan, baik melalui konsultasi, mediasi, negosiasi, konsiliasi, maupun penilaian ahli. Undang-undang dimaksudkan untuk mengatur penyelesaian sengketa di luar forum pengadilan dengan memberikan kemungkinan dan hak bagi para pihak yang berselisih untuk menyelesaikan sengketa atau perbedaan pendapat antara para pihak dalam suatu forum yang lebih sesuai dengan keinginan para pihak. Sebuah forum diharapkan dapat mengakomodir kepentingan para pihak yang bersengketa. Kata kunci: Peradilan Agama, Sengketa Ekonomi Syariah, Non-litigasi, Alternative Dispute Resolution